2017
DOI: 10.4314/jmbs.v6i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Entonox and Transcutaneous Electrical Nerve Stimulation (TENS) in Labor Pain

Abstract: One of the concerns among mothers for delivery is labor pain. There are various methods to decrease labor pain, of which epidural anesthesia is an effective one, but not all mothers agree to receive this invasive intervention. Transcutaneous electrical nerve stimulation (TENS) is an inexpensive, safe, and easily applicable method which can be used in patient control mode. To find proper non-invasive methods to pain relief during labor this study was conducted to compare TENS, Entonox and combination of them du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A study by Chaichian et al 28 revealed a shorter active phase of labor for women who remained immersed in warm water throughout labor than for those who received conventional care. 29 …”
Section: Discussionmentioning
confidence: 99%
“…A study by Chaichian et al 28 revealed a shorter active phase of labor for women who remained immersed in warm water throughout labor than for those who received conventional care. 29 …”
Section: Discussionmentioning
confidence: 99%
“…The frequently used type of sham-TENS was inactive units (in 11 out of 13 studies), though this method is prone to bias as it is not clear if the parturient or the investigator were blinded to the treatment. Since the Cochrane review, several RCTs have been published in which 5 out of 7 studies were graded +++ on GRADE (28,64,75,117,119).…”
Section: Key Findings Of Study Imentioning
confidence: 99%
“…In Study II and Study III, several improvements could be made with respect to optimizing the placements of electrodes and parameters of TENS, including pulse duration and frequency. Therefore, it was decided to go for long pulse durations and individually adjusted intensity, which has proven effective in other studies (28,64,85,103,119). However, electrode placement in studies II and III was only achieved with one set of electrodes at the S2-S4 spinal level.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation